Surveillance of soil-transmitted helminths and other intestinal parasites in shelter dogs, Mississippi, USA - Huan Zhao; Patsy A. Zendejas-Heredia; Vito Colella; Irene Arguello; Kai Brookes; Indu S. Panicker; John M. Williams; Kayla N. Patterson; Gurbaksh Singh; Charlotte V. Hobbs; Richard S. Bradbury (One Health, 2025)
In recent years, soil-transmitted helminthiases, including strongyloidiasis have become a prominent public health concern in the southeastern United States of America (USA). While there is ongoing human soil-transmitted helminths (STH) surveillance in Mississippi and Alabama, very little attention has been paid to potentially zoonotic STH from dogs in this region. We microscopically examined faecal samples collected from 252 shelter dogs in Mississippi using the formalin-ethyl acetate sedimentation method. Extracted DNA were subjected to three multiplex real-time polymerase chain reaction (qPCR) assays targeting canine STH (canine hookworm species, Strongyloides spp., Toxocara species and Baylisascaris procyonis). The combined prevalence of STH by microscopy and qPCRs in Mississippi dogs was 62.7 %, with hookworms at 50.0 % and Toxocara at 24.2 %. qPCR identified Ancylostoma caninum (44.4 %), Toxocara canis (22.2 %), Strongyloides spp. (1.2 %), and Uncinaria stenocephala (0.8 %). No other canine hookworm species, Baylisascaris procyonis, or Toxocara cati were detected by qPCR. Seven additional intestinal parasites were identified by microscopy, including Trichuris vulpis (13.5 %), Physaloptera sp. (6.4 %), Cystoisospora sp. (3.2 %), Dipylidium caninum (1.2 %). Giardia duodenalis (0.8 %), Alaria sp. (0.4 %), and Macracanthorhynchus sp. (0.4 %). These findings, combined with recent human cases in Mississippi, highlight the need for targeted public health messaging to promote regular anthelmintic treatment for dogs and their owners.